The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21307/acee-2018-061
|View full text |Cite
|
Sign up to set email alerts
|

A Gis Based Graph Oriented Algorithmic Model for Poly-Optimization of Waste Management System

Abstract: The methodology of modelling and object analysis of management systems includes, inter alia, operations connected with the definition of special object types being an imitation of components (objects-sources of waste generation, objects for waste neutralisation, networks of roads, natural environment components, waste substances, etc.) [4, 6-7]. Since the systems are investigated in the GIS technology, some objects are assigned attributes of spatial representation (location coordinates, geometric and graphic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 16 publications
1
16
0
2
Order By: Relevance
“…In connection with this, the scientific discussions more and more often draw attention to the issue of the so-called ecological security. The priority here is proper waste management, and in particular, taking actions so that the largest possible quantities of wastes can be re-used [1,2]. This activity is not only intended to prevent the formation of unwanted waste heaps, but also aims to reduce the extraction of natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…In connection with this, the scientific discussions more and more often draw attention to the issue of the so-called ecological security. The priority here is proper waste management, and in particular, taking actions so that the largest possible quantities of wastes can be re-used [1,2]. This activity is not only intended to prevent the formation of unwanted waste heaps, but also aims to reduce the extraction of natural resources.…”
Section: Introductionmentioning
confidence: 99%
“…For instance Helms and Heidt [17] found that up to 6% of NO x (and up to 10% of PM) traffic related emissions in Germany are caused by mobile construction machinery. Under the assumption, that concentrations in the air in a case of emission sources of low height, are proportional to emissions (what is fulfilled roughly in city-centers) and taking into consideration the 48% share of NO x emission from road-transport sector in total [24,25,26,27] (39% road transport + 9% nonroad transport), the share of construction machines in total NO x concentration yields about 3%. The similar calculations made by Millstein and Harley [18], which assigned 11% of NO x (and 14% of total 1-hour NO 2 level in the air in the vicinity of the conducted construction works was not exceeded.…”
Section: Discussion Of Results and Con-clusionsmentioning
confidence: 99%
“…Recovery of energy from the municipal waste should constitute a method that is complementary to recycling and leads to the decrease of the stream of waste directed to landfills. From the energetic and economic point of view, some fractions selected from the stream of municipal waste constitute precious energetic material [8][9][10][11][12][13]. This management method has another advantage -it can cover all types of waste -especially non-uniform and contaminated for example with organic fraction [13][14][15][16][17].…”
Section: Methods Of Energy Recovery From the Wastementioning
confidence: 99%